أثر العُرف في أبواب القتل: دراسة فقهية على المذهب المالكي: (The Impact of Custom in Cases of Homicide: A Jurisprudential Study According to the Maliki School) - سميرة حسن سالم البلعزي; نور فاهمة محمد رزيف; شهيدرا عبد الخليل (At-Tajdid - Intellectual Refereed Journal, 2025)
This study explores the influence of custom (ʿurf) on homicide classifications within the Mālikī school of Islamic law by analyzing relevant Mālikī fatwas to assess the practical role of customary practices in criminal adjudication. While the application of ʿurf in criminal law remains underexamined, its potential significance in shaping legal outcomes—particularly in serious matters such as homicide—warrants detailed investigation. Employing both inductive and analytical methodologies, the research considers custom as a supplementary legal source alongside Mālikī jurisprudential principles. The findings reveal that ʿurf plays a substantive role in criminal rulings, especially in areas involving ḥudūd, qiṣāṣ, diyah, and taʿzīr. Although custom has limited influence in cases governed by fixed Sharīʿa penalties, it significantly affects rulings related to the classification and causality of killings, liability in animal-caused deaths, the duration of crucifixion for ḥirābah (armed robbery), definitions of intimidation in homicide, forgiveness in qiṣāṣ without diyah, the role of an absent heir (walī al-dam) in initiating retribution, cases involving mental incapacity, the financial liability of the extended family (ʿaqīlah), the use of tribal oath (qasāmah), and the implementation of discretionary punishments (taʿzīr) in accordance with prevailing customs. Keywords: Legal Effect, ʿUrf (Custom), Homicide, Mālikī School